Pengaruh Media Panorama dan Wordwall dalam Pembelajaran Pendidikan Pancasila Terhadap Minat Belajar Peserta Didik Kelas V SDN Pulorejo 01 - Afitri Diah Utami; Erviana Tri Rahayu; Susilo Tri Widodo; Rina Nuraeni; Esti Wulandari (Journal on Education, 2024)
Someone who has an interest will be stimulated to be enthusiastic about an activity, including studying. Students' learning interest can be influenced by the learning media implemented by the teacher during the learning process. This research aims to determine the effect of using panorama and Wordwall learning media and compare the effectiveness of the two media in learning Pancasila Education on the learning interest of class V students at SDN Pulorejo 01. This research uses the Classroom Action Research method. The data analysis technique used in this research is descriptive qualitative. From the teaching practice activities that have been carried out by the author by applying panorama and wordwall media in Pancasila education learning in class V at SDN Pulorejo 01, it can be seen that these two media have an influence on the learning interest of class V students at SDN Pulorejo 01. The students were initially passive and less active becomes more active after using learning media in teaching and learning activities. Based on the research that has been carried out, the most effective way to apply Pancasila education for class V at SDN Pulorejo 01 is wordwall.